2022
DOI: 10.5937/inovacije2203075b
|View full text |Cite
|
Sign up to set email alerts
|

Children's understanding of thermal phenomena in initial science instruction

Abstract: The method of interpreting thermal phenomena in the lower grades of primary school, which avoids explaining these phenomena based on the particle structure of a substance, gives room for pupils' alternative ideas. The aim of this paper is to determine the level of pupils' understanding of thermal phenomena in the lower grades of primary school. For this purpose we developed a test of knowledge of the following concepts: aggregate states of a substance, substance structure, temperature, heat, and heat conductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…The best results were achieved by the third grade students, and, expectedly, the worst were the second graders. In this study, similar to our previous study (Balać et al, 2022), it was found that the fourth graders have lower achievements comparing to the third graders. That could be explained by the significantly smaller volume of content on magnetism in the fourth grade curriculum, as well as the insufficient durability of the knowledge acquired in the previous year.…”
Section: Discussionsupporting
confidence: 91%
“…The best results were achieved by the third grade students, and, expectedly, the worst were the second graders. In this study, similar to our previous study (Balać et al, 2022), it was found that the fourth graders have lower achievements comparing to the third graders. That could be explained by the significantly smaller volume of content on magnetism in the fourth grade curriculum, as well as the insufficient durability of the knowledge acquired in the previous year.…”
Section: Discussionsupporting
confidence: 91%
“…Teaching that enables acquirement of scientific concepts have to be individualized and in correlation with the development level of a student (Klausmeier, 1985). It is well established that children explain the world arround them in a manner that is acceptable to them, and that, prior to starting school, they already possess, and further during their education, continue to adopt numerous false ideas (misconceptions) about scientific contents featured in the curriculum (Pine et al, 2001;Dimitriou & Christidou, 2007;Balać, Bošnjak Stepanović, Bogdanović, 2022;Blagdanić, Radovanović, Bošnjak Stepanović, 2019). There are plenty of sources for developing misconceptions and the most emphasized are: Children's experiences, ignorance of the elders (parents and teachers) and influence of peers.…”
Section: Introductionmentioning
confidence: 99%